Carrying Capacity Assessment Based on Chlorophyll-a in The Bandar Kayangan Lembah Sari Reservoir Rumbai Pesisir District Pekanbaru city Riau Province - Ricki Meno P Sinurat; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractA study aimed to assess the aquatic carrying capacity in the Bandar Kayangan Lembah Sari Reservoir, Rumbai Pesisir District, Pekanbaru City, Riau Province. The carrying capacity was determined based on primary productivity using chlorophyll-a concentration, which is indicating the existence of phytoplankton in waters. This research was conducted April-May 2018. Samples were taken at 4 station, namely Station 1 (inlet from the Merbau River), Station 2 (inlet from Ambang River) Station 3 (transition zone) and Station 4 (around the dam or outlet). In each stations, a sampling point is determind, namely the surface and the water column. Sampling was done three times once/week. Water quality parameters measured were chlorophyll-a concentration, transparency, temperature, pH, dissolved oxygen, free carbon dioxide, nitrate and phosphate. Results shown that chlorophyll-a concentration : 12.54-19.82 µg/L, transparency : 65.17-74.33 cm, temperature : 27.3-29.3 ºC, pH: 5, dissolved oxygen : 4.1-7.69 mg/L, : 3.32-7.32 mg/L, nitrate : 0.01-0.03 mg/L, and phosphate : 0.01-0.03 mg/L. Based on chlorophyll-a concentration the carrying capacity of Bandar Kayangan Lembah Sari Reservoir was 4,53 tonnes of fish/year.Keywords: Carrying capacity, Bandar Kayangan Reservoir, Chlorophyll-a